2012
DOI: 10.1016/j.ajpath.2011.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Gene Deletions and Amplifications in Human Hepatocellular Carcinomas

Abstract: Tissues from 98 human hepatocellular carcinomas (HCCs) obtained from hepatic resections were subjected to somatic copy number variation (CNV) analysis. Most of these HCCs were discovered in livers resected for orthotopic transplantation, although in a few cases, the tumors themselves were the reason for the hepatectomies. Genomic analysis revealed deletions and amplifications in several genes, and clustering analysis based on CNV revealed five clusters. The LSP1 gene had the most cases with CNV (46 deletions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 67 publications
5
70
0
Order By: Relevance
“…On the one hand, hepatic aneuploidy could have pathological consequences. Aneuploidy has been extensively described in hepatocellular carcinoma (28)(29)(30), but it is unknown whether tumors arose from preexisting aneuploid hepatocytes or simply became aneuploid during tumorigenesis. It is intriguing that whole chromosome gains/losses were reported in dozens of lesions (28).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, hepatic aneuploidy could have pathological consequences. Aneuploidy has been extensively described in hepatocellular carcinoma (28)(29)(30), but it is unknown whether tumors arose from preexisting aneuploid hepatocytes or simply became aneuploid during tumorigenesis. It is intriguing that whole chromosome gains/losses were reported in dozens of lesions (28).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in CCA development, N1ICD association with protein kinase B signaling in hepatocytes stimulated their malignant dedifferentiation (82). The stimulation of N1ICD expression by inflammatory mediators has also been reported in human CCA, which additionally supports the role of Notch in liver cancer (83) (Table II) (9,12,24,31,(84)(85)(86)(87).…”
Section: Role Of Notch In Hcc and Icc Developmentmentioning
confidence: 54%
“…Comparison of proteomics analysis from primary fibroblast cultures derived from morphologically normal colonic mucosa of familial adenomatous polyposis patients with those obtained from unaffected controls RSU-1 down-regulated in six human polyposis samples compared to six samples from morphologically normal colonic mucosa [12] Hepatocellular carcinoma Somatic copy number variation (CNV) analysis in 98 hepatocellular carcinoma samples RSU-1 gene exhibited a high frequency of CNVs (9 out of 98 samples) with 7 deletions and 3 amplifications present in the RSU-1 gene [14] High-grade gliomas Southern blotting…”
Section: Type Of Lesion Methodsology Observation Related To Rsu-1 Refementioning
confidence: 99%
“…Furthermore, a somatic copy number variation (CNV) analysis of 98 hepatocellular carcinoma samples showed that the RSU-1 gene exhibited a high frequency of CNVs (9 out of 98 samples) with 7 deletions and 3 amplifications present in the RSU-1 gene, indicating that RSU-1 gene is frequently deleted in human liver cancer [14] .…”
mentioning
confidence: 99%